Need for integration of hepatitis C (HCV) services in community-based settings for people who inject drugs: results from a global values and preferences survey - M. Di Ciaccio; V. Villes; C. Perfect; J. L. El Kaim; M. Donatelli; C. James; P. Easterbrook; R. M. Delabre (BMC, 2023)
Abstract Background To inform the development of updated World Health Organization (WHO) guidelines on simplified service delivery for HCV infection, a global survey was undertaken among people affected or infected by HCV. The objective of this analysis is to identify specific needs and preferences among people who inject drugs. Methods A multi-country, anonymous, self-administered online survey conducted in 2021 was developed by Coalition PLUS and the World Hepatitis Alliance in partnership with the WHO. Preferences for test and treat locations and simplifying HCV care were collected among people affected or infected by HCV. Chi-square tests were used to compare respondents who identified with current or former injection drug users through identification with key population to other respondents who did not identify with this key population. Results Among 202 respondents, 62 (30.7%) identified with current/former injection drug users. Compared to other respondents, they were: older [median (IQR): 48 (36-57) vs. 39 (31-51) years, p = 0.003]; more likely to have been tested for HCV (90.2% vs. 64.3%, p = 0.001); more likely to prefer testing in a community-based centre (CBC) (55.4% vs. 33.3%, p = 0.005); or in a support centres for people who use drugs (SCPUD)(50.0% vs. 9.8%, p < 0.001). The most important considerations regarding testing locations among people identified with current/former injection drug users (compared to the other respondents) were: non-judgemental atmosphere (p < 0.001), anonymity (p = 0.018) and community worker (CW) presence (p < 0.001). People identified with current/former injection drug users were more likely to prefer to receive HCV treatment in a CBC (63.0% vs. 44.8%, p = 0.028) or in a SCPUD (46.3% vs. 9.5%, p < 0.001), compared to the other respondents. The most important considerations regarding treatment locations among people identified with current/former injection drug users were the non-stigmatising/non-judgemental approach at the site (p < 0.001) and the presence of community-friendly medical personnel or CW (p = 0.016 and 0.002), compared to the other respondents. Conclusion The preferences of people identified with current/former injection drug users indicated specific needs concerning HCV services. Integration of HCV services in community-based risk reduction centres may be an important element in the development of adapted services to increase uptake and retention in HCV care among this population.